GENERATION OF ABSTRACT MEANING REPRESENTATION WITH GRAPH SEQUENCE ITERATIVE INFERENCE APPROACH - Tobing Alexandro, Christian
This paper presents an Indonesian AMR parser that uses a one-stage parsing approach. One- stage parsing is a technique for parsing natural language sentences into Abstract Meaning